2017
DOI: 10.1186/s12885-017-3587-8
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genomic profiling in routine clinical practice leads to a low rate of benefit from genotype-directed therapy

Abstract: BackgroundDescribe a single-center real-world experience with comprehensive genomic profiling (CGP) to identify genotype directed therapy (GDT) options for patients with malignancies refractory to standard treatment options.MethodsPatients who had CGP by a CLIA-certified laboratory between November 2012 and December 2015 were included. The medical records were analyzed retrospectively after Institutional Review Board (IRB) approval. The treating oncologist made the decision to obtain the assay to provide poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 24 publications
3
36
0
1
Order By: Relevance
“…The idea of being able to treat all patients, each with a drug suitable for the specific alterations of his tumour, is certainly attractive for oncologists and especially for patients. In our work, we evaluated the feasibility of First, we evaluated the overall success rate, which was lower (68.85%) than in other similar works, [9][10][11][12] due to several reasons. Foremost, in a significant percentage of cases, tissue qualification was not performed locally before the shipment: a local preassessment could potentially reduce the failure rate.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The idea of being able to treat all patients, each with a drug suitable for the specific alterations of his tumour, is certainly attractive for oncologists and especially for patients. In our work, we evaluated the feasibility of First, we evaluated the overall success rate, which was lower (68.85%) than in other similar works, [9][10][11][12] due to several reasons. Foremost, in a significant percentage of cases, tissue qualification was not performed locally before the shipment: a local preassessment could potentially reduce the failure rate.…”
Section: Discussionmentioning
confidence: 98%
“…They found similar genes and pathway involved to our work with higher percentage of patients treated with genotype directed therapy (12%-35%). [9][10][11][12] Considering the time of follow-up of our study (in most of patients F1CDx was performed in the last 6 months of the study), and the fact that many patients did not progress to their ongoing therapies, probably we will reach this percentage during next years. Indeed, a good number of prospective [17][18][19][20][21][22][23] and retrospective [24][25][26][27] trials evaluated CGP using different techniques (NGS, WES, WGS) but in the context of large academic centres.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, mostly from large academic centers, have reported successful implementation of CGP and have shown that most patients will have at least one potentially actionable genomic alteration on CGP. In a retrospective study of 125 patients who underwent CGP, clinically relevant genetic alterations were found in 111 (92%) patients [15]. Only 15 (12%) patients received molecularly targeted therapy, with three who derived clinical benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Payers have potentially overlooked CGP as a sophisticated testing approach that informs complex clinical decision-making and enables a patient’s next best care option, be it drug therapy or no further treatment. A few studies have assessed the benefits of CGP for treatment decisions, but results often have limited generalizability with patients tested in the context of prospective studies intended to enroll patients in targeted therapy trials [1318], limited histologies [19], using retrospective physician questionnaires with modest response rates at the patient level [20, 21], or most commonly, in the context of large academic center molecular tumor boards [2226].…”
Section: Introductionmentioning
confidence: 99%